Mapping Global Research on Instructional Media and STEM Education: A Bibliometric Analysis - Alfahani, Khairul; Muthie, Imam; Hendri, Nofri; Masriani, Elsa (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to map and analyze global trends in the use of digital learning media in STEM (Science, Technology, Engineering, and Mathematics) education through bibliometric analysis. Using data from journals indexed in Scopus, this study employs a Systematic Literature Review (SLR) approach to identify research patterns and areas that require further attention. The analysis results indicate that between the years 2015 and 2024, there was a significant increase in the number of publications, peaking in 2024, with 24 documents published. The United States emerged as the main contributor with 51 documents, emphasizing the dominance of educational institutions in the country. Additionally, keywords such as 'digital media,' 'STEM,' and 'learning media' highlight a major focus on the integration of technology in learning. Nevertheless, the number of publications still below 1000 documents indicates that there are still many aspects to explore. This research shows that digital learning media in STEM education is increasingly favored by educators. With the growing attention from researchers and academics in conducting studies on digital learning media and STEM, support from the government and more in-depth research must be developed. Recommendations for further research include deeper exploration of technology integration methods and their impact on student learning outcomes, as well as considering local contexts and languages in research. Thus, this research makes an important contribution to the literature and paves the way for more contextual research in the future.